Rainfall frequency analysis for the "pantanal Mato-Grossense", Brazil - García, Eduardo Alfonso Cadavid; Castro, Luís Hernán Rodríguez (Pesquisa Agropecuaria Brasileira, 2014)
Eighty-one daily rainfall series from the Alto Paraguai hydrographic basin containing the "Pantanal" were anlysed DNOS data were used to obtain natural groups with certain homogeneity and to analyse the probability concerning 7, 15 and 30 day periods of rainfall occurrence. The techniques used were: principal components and cluster analysis, applying the Ward method; the expected rainfall occurrence was given by the gamma distribution f(X) = 1/(ßαГ(α)) .xα-1 exp. (-x/ß); α, ß> 0 adjusted by central moments method, followed by the Kolmogorov-Smirnov test for fitting. Main results: five main groups were defined: the first group, with 20 climatic stations located in the north-east of the basin, with intense rainfall concentrated in November/March, and mesothermal humid climate; the second group, with 41 stations (Pantanal) with megathermal humidsec climate; the third group with mesothermal sub-humid climate. The best fittings for the gamma distribution were observed for the 30-day periods.